ค่าเทียบเท่ารถยนต์นั่งส่วนบุคคลสำหรับรถบรรทุกและรถประจำทางบนทางหลวงสองช่องทางจราจรในระเทศไทย - วิสูตร แสงอรุณเลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The planning and geometric design of two-lane highways in Thailand has traditionally adopted the Passenger Car Equivalents (PCEs) evaluated in other countries. However, these PCEs may not be the proper values to represent the traffic situation in Thailand. This thesis strives to determine the PCEs for accurately representing the effects of trucks and buses on the traffic on rural two-lane highways in Thailand. The so-called Median Stream Speed, Platoon Leaders, and Platoon Followers techniques were chosen for evaluating the PCEs. The collection of required traffic data was carried out on Highway Route Number 36 in the Chonburi and Rayong provinces. The PCEs derived from the Platoon Leaders technique appeared more sensible than those obtained from the other two techniques. The study found that the PCEs of a particular type of heavy vehicles on two-lane highways increase with the vertical gradient of roadway. For flat grade, the estimated PCE values using the Platoon Leaders technique for six wheelers, ten wheelers, truck combinations, and buses were 2.49, 3.20, 3.94, and 1.67 respectively. The PCEs derived from the data observed over the 200 m. highway sections with about 2% gradient were 2.63, 3.76, 4.46, and 2.06 for six wheelers, ten wheelers, truck combinations, and buses respectively. At the 200 m. sections with about 3% gradient, the resulting PCEs for six wheelers, ten wheelers, truck combinations, and buses were 2.86, 4.34, 6.17, and 2.43 respectively.